Problem Solving the Hungarian Way (Part 2) (pp. 9–15) - Walker, Janet M.; Scanga, Bridget C (Ohio Journal of School Mathematics, 2019)
Lajos Posa (pronounced Posha) is one of the most prominent mathematics educators in Hungary. The authors introduce readers to the Posa's technique of developing numerous methods as a means to foster student mathematical understanding. The authors illustrate the approach through exploration of multiple solution strategies for the 1000 square task.